When the Internet Becomes X-Rated: Creating an Ethical Climate for Technology in Catholic Schools - Kosse, Susan Hanley (Catholic Education: A Journal of Inquiry and Practice, 2001)
Pornography is the number-one business on the Internet, yet the very same Internet can be a valuable source of knowledge for all students. Educational leaders face many challenges in bringing the Internet into classrooms. This article reviews recent and relevant case law on Internet access in schools, offers guidance about the writing of effective acceptable use policies, and concludes with advice to Catholic school teachers and administrators on creating an ethical climate while fully using available technology.